Efectos de las bacterias nitrificantes en la producción del cultivo de fréjol (Phaseolus vulgaris, L.) - Rivera Moreno, Jimmy Rolando (2024)
Bean production in Ecuador constitutes one of the most relevant agricultural and economic activities, taking place mainly in the valleys of the provinces of Carchi, Imbabura, Loja, Chimborazo and Bolívar. The objective was to analyze the effect of nitrifying bacteria on the production of bean crops (Phaseolus vulgaris L.). Information was collected from magazines, virtual libraries and the latest scientific articles. The method used was bibliographic research, with information collection techniques. The conclusions determined that nitrifying bacteria carry out the transformation of ammonia into nitrates, a process known as nitrification, which are used by both plants and denitrifying bacteria. Plant roots absorb nitrogen from the soil in the form of nitrate (NO3-) or ammonium (NH4+). In most soils, the activity of nitrifying bacteria facilitates the predominant uptake of nitrate (N-NO3-) by crops. Nitrogen-fixing bacteria contribute biologically to meeting a portion of the crop's nitrogen demands. It slows down the aging rate of plant cells, thus prolonging their photosynthetic capacity. The biological fixation of nitrogen carried out by diazotrophic bacteria has allowed a significant increase in the yield of bean crops, while at the same time it has decreased the dependence on nitrogen fertilizers and the emission of harmful gases, such as nitrous oxide (N2O), which which in turn has generated economic benefits.